Measuring the Economic Impact of Integrating Digital Business Information Systems and Digital Marketing on Operations and Profitability - Aristyawati, Ni Kadek; Maradona , Agus Fredy (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to identify the role of digital business information systems in improving the operational efficiency of villas in Ubud, identify the impact of digital marketing strategies to increase the profitability of villas in Ubud, identify the effect of integration between digital business information systems and digital marketing to improve profitability and operations in Ubud villas, as well as to determine the significance of the contribution of integration of digital business information systems and digital marketing in improving the quality of Service and customer satisfaction in Ubud villas. The type of data used in the study is quantitative data. The results showed that digital business information systems have a significant role in improving the operational efficiency of villas in Ubud. This technology facilitates more effective operational management. On the other hand, digital marketing strategies are proven to contribute positively to increasing villa's profitability, although their effect on operational efficiency is statistically insignificant. Integration between digital information systems and digital marketing has a stronger positive impact on operational efficiency and profitability, showing that the combination of these two factors is more effective than implementing each separately. In addition, this integration also improves the quality of Service and customer satisfaction, which in turn strengthens the competitiveness of the villa. Overall, these findings emphasize the importance of an integrated approach between Information Technology and digital marketing in achieving optimal operational and financial results in the villa sector in Ubud.